Biologia e ecologia comparativas de Cichla Kelberi e Cichla Piquiti (Cichliformes, Cichlidae) no reservatório da UHE de Lajeado, rio Tocantins - Andrade, Geovana de Souza (Universidade Federal do Tocantins, 2022)
n the Tocantins River Basin there are two species of the genus Cichla that live in sympatry, Cichla kelberi and C. piquiti. Cichla piquiti is more abundant than its congener C. kelberi. The aim of the study was to compare the ecology and biology of C. kelberi and C. piquiti in the Lajeado HPP reservoir. Between 2010 and 2020, monthly samplings were carried out, from 8:00 am to 6:00 pm, in different points and habitats. For each captured individual, biometric and morphometric data were recorded. In addition, there was identification of sex, stage of sexual maturation, degree of gastric repletion and estimated fertility. Cichla piquiti had more significant results for ecological factors related to population structure, as well as greater body size and schooling. Diet did not differ between species, showing that they consume the same resources. Cichla piquiti had a longer reproductive period and better body condition. Considering the analyzed ecomorphological patterns, the attributes related to locomotion were highlighted, indicating that C. piquiti has greater swimming and sprinting power. This work showed that, due to its high abundance, when compared to the abundance of the congener C. piquiti, which is well established in the reservoir.